Debridement Techniques in Pediatric Trauma and Burn-Related Wounds - Block, Lisa (Adv Wound Care (New Rochelle), 2015)
Significance: Traumatic injuries are the leading cause of morbidity and mortality in children. The purpose of this review is to provide an overview of the initial assessment and management of traumatic and burn wounds in children. Special attention is given to wound cleansing, debridement techniques, and considerations for pain management and psychosocial support for children and families. Recent Advances: Basic and translational research over the last 5–7 years has advanced our knowledge related to the optimal care of acute pediatric traumatic and burn wounds. Data concerning methods, volume, solution and timing for irrigation of acute traumatic wounds, timing and methods of wound debridement, including hydrosurgery and plasma knife coblation, and wound dressings are presented. Additionally, data concerning the long-term psychosocial outcomes following acute injury are presented. Critical Issues: The care of pediatric trauma and burn-related wounds requires prompt assessment, pain control, cleansing, debridement, application of appropriate dressings, and close follow-up. Ideally, a knowledgeable multidisciplinary team cares for these patients. A limitation in the care of these patients is the relative paucity of data specific to the care of acute traumatic wounds in the pediatric population. Future Directions: Research is ongoing in the arenas of new debridement techniques and instruments, and in wound dressing technology. Dedicated research on these topics in the pediatric population will serve to strengthen and advance the care of pediatric patients with acute traumatic and burn wounds.